Job Satisfaction Gen-Z: A Systematic Literature Review - Anggapradja, Indra Taruna; Marianti, Maria Merry; Deti, Regina (Nomico, 2024)
The study examines the importance of human resource management (HRM) in attracting, retaining, and managing employee performance. It highlights the role of HRM in organizing compensation, benefits, and creating a positive work environment to improve job satisfaction and productivity. The research focuses on Generation Z’s preferences for job satisfaction, including flexibility, work-life balance, and meaningful work. It discusses how managers must adapt to retain young employees and invest in their development and well-being. Utilizing bibliometric analysis and PRISMA guidelines, the study analyzes scientific publications to understand the factors influencing job satisfaction among Generation Z. The study concludes that job satisfaction is crucial for employee retention and creating a positive workplace culture. It suggests that businesses must adapt to the changing needs of Generation Z by focusing on employee satisfaction to improve performance and reduce turnover